Insights into Bacterial Community Involved in Bioremediation of Aged Oil-Contaminated Soil in Arid Environment. (June 2021) - Rahmeh, Rita; Akbar, Abrar; Kumar, Vinod; Al-Mansour, Hamad; Kishk, Mohamed; Ahmed, Nisar; Al-Shamali, Mustafa; Boota, Anwar; Al-Ballam, Zainab; Shajan, Anisha; Al-Okla, Naser
Soil contamination by hydrocarbons due to oil spills has become a global concern and it has more implications in oil producing regions. Biostimulation is considered as one of the promising remediation techniques that can be adopted to enhance the rate of degradation of crude oil. The soil microbial consortia play a critical role in governing the biodegradation of total petroleum hydrocarbons (TPHs), in particular polycyclic aromatic hydrocarbons (PAHs). In this study, the degradation pattern of TPHs and PAHs of Kuwait soil biopiles was measured at three-month intervals. Then, the microbial consortium associated with oil degradation at each interval was revealed through 16S rRNA based next generation sequencing. Rapid degradation of TPHs and most of the PAHs was noticed at the first 3 months of biostimulation with a degradation rate of pyrene significantly higher compared to other PAHs counterparts. The taxonomic profiling of individual stages of remediation revealed that, biostimulation of the investigated soil favored the growth of Proteobacteria, Alphaprotobacteria, Chloroflexi, Chlorobi, and Acidobacteria groups. These findings provide a key step towards the restoration of oil-contaminated lands in the arid environment.